2021
DOI: 10.1111/cea.14029
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 immunity‐driven diseases: Towards a multidisciplinary approach

Abstract: Atopic dermatitis (AD), allergic rhinitis (AR), chronic rhinosinusitis with (CRSwNP) or without (CRSsNP) nasal polyps and asthma share a complex interplay between a genetic background, a polarized immune response and the environment. Their increasing prevalence in urban areas in comparison with rural areas further highlights the role of environmental factors in their development. 1 Interestingly, they can succeed themselves or coexist at the same time in a single individual throughout life. For example, atopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 165 publications
(205 reference statements)
0
27
0
Order By: Relevance
“…Patient participation, prediction of treatment success, prevention of disease and personalized care will help to choose the best specific treatment for the global airway and skin of the patient and will help increase patient satisfaction, therapy compliance and disease control ( 28 ). Furthermore, a multidisciplinary approach by the implementation of integrated care pathways (ICPs) could help to focus on the prevention, detection, non-pharmacological management and treatment of Type 2 comorbidities ( 2 , 12 , 29 32 ). According to our findings, this holistic approach requires assessment of patients across the following key domains: GPs, psychological services, pulmonologists, dermatologists and ENT specialists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patient participation, prediction of treatment success, prevention of disease and personalized care will help to choose the best specific treatment for the global airway and skin of the patient and will help increase patient satisfaction, therapy compliance and disease control ( 28 ). Furthermore, a multidisciplinary approach by the implementation of integrated care pathways (ICPs) could help to focus on the prevention, detection, non-pharmacological management and treatment of Type 2 comorbidities ( 2 , 12 , 29 32 ). According to our findings, this holistic approach requires assessment of patients across the following key domains: GPs, psychological services, pulmonologists, dermatologists and ENT specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing communication exchange between first-, second- and third-line health care providers will contribute to the continuity of care, multidisciplinary evaluation and regular follow-up of patients. However, further clinical trials to assess multidisciplinary approaches in comparison to standard care are still needed to better document the improvement of overall care and outcome of patients with Type 2 inflammation ( 2 , 30 ). Additional themes cited by patients for future research projects are mainly the following: connection between lungs-nose-skin, causes of Type 2 inflammation, effect of COVID-19 on chronic respiratory diseases, link between food and Type 2 inflammation and new treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, in macaques, scRNA-seq found that IL-4 and IL-13 were particularly highly produced by recruited mast cells, indicating that there may be some species specific variation in the cell types that are producing type 2 cytokines ( 15 ). Beyond IL-4 and IL-13, it seems likely that other cytokines and signals are also required to drive necrotic granuloma formation, as elevated levels of IL-4 and IL-13 are observed in many inflammatory responses that do not lead to granuloma formation ( 80 ). The identity of these potential accessory factors is unknown, but experiments characterizing the induction of the epithelial cell-cell adhesion molecule E-cadherin in macrophages in culture found that E-cadherin induction by IL-4 and IL-13 could be enhanced by costimulation with IL-10 and TGFβ ( 52 ), suggesting that these two cytokines may act as accessory factors, facilitating granuloma formation through potentiation of the macrophage-epithelial transitions that underlie granuloma formation ( 46 ).…”
Section: Molecular Reprogramming Of Macrophages and Host Determinants...mentioning
confidence: 99%